FLUX JUMPING IN TYPE-II SUPERCONDUCTORS - Taylanov, Nizom; Toshpulatova, Dildora; O’rozov , Abdixoliq; Narimanov, Bahodir (Физико-технологического образование, 2021)
We have studied the space-time evolution of the thermal and electromagnetic perturbation in a superconductor with the nonlinear current-voltage characteristic in the flux creep regime, theoretically. On the basis of a linear analysis of a set of differential equations describing small perturbations of temperature and electromagnetic field we found that, under some conditions a branching instability may occur in the sample.